THE USE OF LKPD BASED ON THE TPACK FRAMEWORK ON THE MATHEMATICAL PROBLEM SOLVING ABILITY OF CLASS X MAN 4 AGAM STUDENTS - Faizah Quratu Aini; Nana Sepriyanti; Andi Susanto (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2022)
This research is motivated by the lack of support for the media used for mathematical problem-solving skills and mathematical dispositions of students in MAN 4 Agam for the 2021/2022 academic year. One way that can be done is to use LKPD based on the TPACK framework. This study aims to find out the mathematical problem-solving ability of students who learn using LKPD based on the TPACK framework higher than the problem-solving ability of students who learn using ordinary LKPD in class X MAN 4 Agam. The results showed that the average value of mathematical problem-solving ability of experimental class students was 73.47 and the control class was 54.51. Hypothesis test using t-test with α = 0,05 at 95% confidence level obtained.